A Man for All Seasons : Monroe Sweetland and the Liberal Paradox - Robbins, William G., 1935- (Book collections on Project MUSE., 2015)
"The life of prominent Oregon political leader Monroe Sweetland spans the spectrum of 20th-century America. Through seven decades, Sweetland experienced the economic collapse of the Great Depression, the unparalleled violence of a nation at war, the divisiveness of Cold War politics, and the cultural and political turmoil of the Vietnam War. Historian William G. Robbins illuminates the wrenching transformation of American political culture in A Man for All Seasons : Monroe Sweetland and the Liberal Paradox. Racial and economic inequalities motivated much of Sweetland's civic life, including his lifelong memberships in the American Civil Liberties Committee, the National Association for the Advancement of Colored People, the Urban League, the Japanese American Citizens League, and the Red Cross, where Sweetland worked repatriating American prisoners of war after Japan's surrender. Robbins' portrait is holistic, exploring Sweetland's socialist beginnings, inconsistencies in his politics--especially during the Cold War--and his regional legacy. He was the most important person in the resurgence of the modern, liberal Oregon Democratic Party from the late 1940s to the 1960s. He joined the National Education Association in 1964 and became the driving force behind the Bilingual Education Act of 1968 and the fight for the age-18 vote, achieved in the ratification of the 26th amendment in 1971. Monroe Sweetland was a nationally prominent figure, whose fights bequeathed to modern America important legislation that shaped its political landscape"--